Trade-off between creativity and productivity in technology-based SMEs performance: policy implications in South Korea. Issue 3 (3rd July 2017) - Sussan, Fiona; Kim, Ki-Chan; Chinta, Ravi R.; Enriquez, John Laurence
ABSTRACT: The digital revolution has impacted the study of innovation in organizations in such a way that research on organizational ambidexterity needs a more phenomenon-driven approach. In light of this identified need, this article examines the performance of small- and medium-sized enterprises (SMEs) in South Korea based on their balance in exploration and exploitation activities. A 2 (explorative: hi, low) × 2 (exploitative: hi, low) conceptual framework is introduced to depict four types of combined ambidexterity in firms and hypothesize that short- and long-term performances vary among these types of firms. Data from more than 2800 hi-tech manufacturing SMEs in South Korea were collected to empirically test the conceptual framework. The results confirmed the hypothesized difference in performance. Firms indeed vary in degrees of explorative and exploitative innovation and thus have positive but imbalanced impact on their performance. Firms that are high (low) in both explorative and exploitative innovation perform best (worst) in longer-term growth. Firms that tilt toward exploitative innovation perform best in short-term profit. The article concludes with important managerial and policy implications.